Rapid inhibition of atherosclerotic plaque progression by sonodynamic therapy. Issue 1 (6th June 2018) - Sun, Xin; Guo, Shuyuan; Yao, Jianting; Wang, Huan; Peng, Chenghai; Li, Bicheng; Wang, Yu; Jiang, Yongxing; Wang, Tengyu; Yang, Yang; Cheng, Jiali; Wang, Wei; et al.
Abstract: Aims: Currently, efficient regimens to reverse atherosclerotic plaques are not available in the clinic. Herein, we present sonodynamic therapy (SDT) as a novel methodology to rapidly inhibit progression of atherosclerotic plaques. Methods and results: In atherosclerotic rabbit and apoE-deficient mouse models, SDT efficiently decreased the atherosclerotic burden within 1 week, revealing a decrease in the size of the atherosclerotic plaque and enlarged lumen. The shrunken atherosclerotic plaques displayed compositional alterations, with a reduction in lesional macrophages and lipids. The rapid efficacy of SDT may be due to its induction of macrophage apoptosis, enhancement of efferocytosis, and amelioration of inflammation in the atherosclerotic plaque. Compared with atorvastatin, the standard of care for atherosclerosis, SDT showed more significant plaque shrinkage and lumen enlargement during 1 week treatment. Furthermore, SDT displayed good safety without obvious side effects. In a pilot clinical trial recruiting the patients suffering atherosclerotic peripheral artery disease, combination therapy of SDT with atorvastatin efficiently reduced progression of atherosclerotic plaque within 4 weeks, and its efficacy was able to last for at least 40 weeks. Conclusion: SDT is a non-invasive and efficacious regimen to inhibit atherosclerotic plaque progression.